Analysis on Level of Effectiveness Teacher Behavior of Science Faculty Members through Percentage Analysis: Examining the Impact of Teacher Behavior on Science Faculty Members' Effectiveness (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Education is the fundamental power and source, which impacts the quality of life. It is the development of every one of those limits in the person, which will empower himher to control hisher environment and satisfy hisher conceivable outcomes. It has accepted more significance today than any time in recent memory, due to its present job. It is adding new dimensions to our present and future situation. Education is the purposeful and systematic impact, applied by the develop individual upon the youthful through guidance, discipline and agreeable development of physical, intellectual, esthetic, social and otherworldly powers of human being as indicated by individual and social need coordinated towards the association of the informed with hisher maker as the last end. Science is one of those human exercises that man has made to satisfy certain human needs and wants. The science teacher ought to have the general characteristics Effective personality Self-certainty Leadership and love for control Patience Affectionate behavior Hard work and duty Impartial behavior and mentality Plain speaking A great communicator of thoughts Studious and learned Sincerity of direction, and exceptional characteristics Thorough knowledge of the historical backdrop of science Knowledge of the methods of teaching science Knowledge of brain science identified with science teaching Knowledge of the new system of examination Knowledge of medical aid Taste for scientific exercises Efficiency in the preparation and utilization of teaching helps Scientific reasoning and demeanor. In this Article we will analyze Teacher Effectiveness and its Dimensions of Science Faculty Members and Level of effectiveness-Teacher behavior-of science faculty members.